Rainfall patterns and critical values associated with landslides in Povoação County (São Miguel Island, Azores): relationships with the North Atlantic oscillation - Marques, Rui (2008)
São Miguel Island (Azores) has been affected by hundreds of destructive landslide episodes in the last five centuries, triggeredeither by earthquakes, volcanic eruptions or rainfall episodes, which were responsible for many deaths and very importanteconomic losses.Among the instability causes, meteorological factors are of primary importance on Povoação County, namely the highrecurrence rate of calamitous rainfall triggering landslides. The most recent catastrophic episode took place on the 31st October 1997 when almost 1000 soil slips and debris flows were triggered, and 29 people died in the Ribeira Quente village.The role of rainfall on regional landslide activity was analysed applying cumulative rainfall methods. The method comprisesthe reconstruction of both absolute and calibrated antecedent rainfalls associated with each major landslide event. Thecritical rainfall combination (amount-duration) responsible for each landslide event was assessed and a rainfall criticalthreshold for landslide occurrence was calculated. Rainfall-triggered landslides in the study area are ruled by the functionID144Ð06D 0Ð5551, and they are related both to short duration precipitation events (1 – 3 days) with high average intensity(between 78 and 144 mm/day) and long-lasting rainfall episodes (1 – 5 months) with a lower intensity (between 9 and22 mm/day).The impact of the North Atlantic Oscillation (NAO) on the regional precipitation regime was evaluated. It is shown thatthe monthly precipitation of S ̃ao Miguel is largely modulated by the NAO mode presenting a significant negative correlationwith the NAO index. This result arises from the NAO control on the travelling latitude of most storm tracks that cross theNorthern Atlantic Ocean.